2016
DOI: 10.1111/trf.13945
|View full text |Cite
|
Sign up to set email alerts
|

GADD45α is involved in the apoptosis of lymphocytes induced by riboflavin and ultraviolet light

Abstract: These data revealed that RF-PRT effectively inhibited proliferation and induced apoptosis of lymphocytes by promoting GADD45α expression, which subsequently activates p38 and JNK signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…Caspase expression was not observed in WBCs following UV + R PRT, suggesting that these cells underwent an alternative caspase‐independent apoptotic pathway. Reports using varying doses of UV exposure suggested that WBCs generally undergo conventional apoptosis, that is, caspase activation, up regulation of GADD45α, CD95 (FAS/APO‐1), Bax, and/or p73, and poly–adenosine diphosphate ribose polymerase cleavage . There are, however, reports of caspase‐independent apoptosis occurring in WBCs in response to other stimuli, or in other cell types in response to UV exposure, providing some precedence for our findings .…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Caspase expression was not observed in WBCs following UV + R PRT, suggesting that these cells underwent an alternative caspase‐independent apoptotic pathway. Reports using varying doses of UV exposure suggested that WBCs generally undergo conventional apoptosis, that is, caspase activation, up regulation of GADD45α, CD95 (FAS/APO‐1), Bax, and/or p73, and poly–adenosine diphosphate ribose polymerase cleavage . There are, however, reports of caspase‐independent apoptosis occurring in WBCs in response to other stimuli, or in other cell types in response to UV exposure, providing some precedence for our findings .…”
Section: Discussionsupporting
confidence: 59%
“…Reports using varying doses of UV exposure suggested that WBCs generally undergo conventional apoptosis, that is, caspase activation, up regulation of GADD45α, CD95 (FAS/APO-1), Bax, and/or p73, and poly-adenosine diphosphate ribose polymerase cleavage. 24,29,34,[46][47][48] There are, however, reports of caspaseindependent apoptosis occurring in WBCs in response to other stimuli, or in other cell types in response to UV exposure, providing some precedence for our findings. 22,[48][49][50] Platelets also demonstrated caspase 9 and 3 activity after UVB exposure with riboflavin using the Mirasol system, but differences were observed 5 days after storage.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations